Expulsion of Fibroids to the Endometrial Cavity after Magnetic Resonance Imaging-guided High Intensity Focused Ultrasound Surgery (MRgFUS) Treatment of Intramural Uterine Fibroids - Jeong, Jae-Hyeok (J Menopausal Med, 2016)
OBJECTIVES: This report seeks to introduce some cases of the patients who received magnetic resonance imaging (MRI)-guided high intensity focused ultrasound (HIFU) surgery (MRgFUS)-based intramural uterine fibroids treatment where the post-MRgFUS intramural uterine fibroids decreased in its volume and protruded towards the endometrial cavity to be expelled by hysteroscopy. METHODS: Of the 157 patients who had received MRgFUS treatment in the Obstetrics and Gynecology of the Hospital from March, 2015 to February, 2016; this study examined 6 of the cases where, after high intensity focused ultrasound treatment, intramural uterine fibroids protruded towards the endometrial cavity to be removed by hysteroscopic myomectomy. The high intensity focused ultrasound utilized in the cases were Philips Achieva 1.5 Tesla MR (Philips Healthcare, Best, The Netherlands) and Sonalleve HIFU system. RESULTS: The volume of fibroids ranged from 26.0 cm(3) to 199.5 cm(3), averaging 95.6 cm(3). The major axis length ranged from 4.0 cm to 8.2 cm, averaging 6.3 cm. Fibroid location in all of the patients was in intramural uterine before treatment but after the high intensity focused ultrasound treatment, the fibroids were observed to protrude towards the endometrial cavity in at least Day 5 or up to Day 73 to allow hysteroscopic myomectomy. CONCLUSIONS: In some cases, after an intramural uterine fibroid is treated with MRgFUS, fibroid volume is decreased and the fibroid protrudes towards the endometrial cavity. In this case, hysteroscopic myomectomy can be a useful solution.